Exploring the nexus of health and happiness: A study on the life satisfaction of urban elderly in India - Raghunath Mandi; Dhananjay W. Bansod (Elsevier, 2023)
Introduction: With increasing age, people experience various crisis like loss of physical, mental, and social status and modification in their roles and responsibilities within family and society and paving their way towards dependency in life. This dependency on others deteriorates quality of life and diminishes life satisfaction. The present study examines the influence of multidimensional health on life satisfaction among urban elderly in India. Method: Based on wave-1 of Longitudinal Ageing Study in India (LASI) 2017-18, Life satisfaction was assessed among urban elderly aged 60 years and above using SWLS scale. Multivariate linear regression analysis was used to investigate the association between multidimensional health, sociodemographic variables and life satisfaction. Results: The overall mean life satisfaction score was 24.94 (SD = 7.20) which is more than many developed countries like Spain, Mexico and China. Elderly having good self-rated health, having higher functional health, and good mental health have been associated with higher life satisfaction while having any depressive symptoms or any impairment was associated with lower life satisfaction among urban elderly. Apart from that, life satisfaction score differs significantly by socio-demographic characteristics. Conclusion: During old age, a sense of companionship and good social networks are essential in enhancing life satisfaction, whereas, perceived physical, mental and functional health are equally important in facilitating self-perception of ageing. Therefore, life satisfaction among elderly should be looked not only from the perspective of individual factors (like health and socioeconomic status) but broad socio-cultural dimensions should be inquired extensively to achieve successful ageing.